Brain Drain in Kosovo: Policy Recommendations for Talent Retention and Sustainable Development - Nimani Mentor; Nimani Arbenita Sylejmani (SEEU Review)
This study investigates the factors influencing emigration intentions among Kosovo's educated youth, with a particular focus on addressing the growing issue of brain drain. Utilizing a mixed-methods approach, the research explores economic, political, and social factors contributing to migration intentions. A survey of 150 respondents aged 18–35 reveals a significant disconnect between educational attainment and local employment opportunities, with high unemployment and underemployment driving dissatisfaction. The findings align with established migration theories, including Push-Pull Theory and Human Capital Theory, illustrating how push factors like political instability and poor job prospects in Kosovo contrast with the pull factors of better salaries and career opportunities abroad. Policy recommendations include increasing wages, improving job opportunities, fostering political stability, and supporting entrepreneurship to mitigate brain drain and promote a sustainable future for educated youth in Kosovo.